Saint Cyprien et les barbares africains (epist. 62) - Kotula, Tadeuz (Antigüedad y Cristianismo, 1990)
The relations between Romans and autochthonous in northern Africa normally must have been pacific although on occasions living together gave rise to problems which resulted in military conflicts. Our knowledge of the evolution of the society in the third century is very poor due to the lack of literary documents. Because of this short comming the epigraphic evidence plays an important role, and also the works of S. Cyprian, written during this period, assumes a position of out standing interest. Around 253, when an insurrection broke out in the eastern part of Mauritania and in Numidia, Cyprian wrote his epistle n. 62 to the eight bishops of the diócesis located in these territories, sending at the same time money to pay the ransom of those captured by the barbarians. The author tries to determine the particularities and the content of the barbarian olTense basing his study on the data provided in the letter and from what we know of the period in that area. The personality of S. Cyprian and his writings are re-examined in order to obtain a deeper knowledge of the third century.